Nurses knowledge about Management Extravasation Intravenous Cytotoxic Medication At Amal National Hospital in Baghdad City - Batool Kadham Hussin1 , Wrood Abdul Razaq Ahmed2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Extravasation, the unintentional leak of an anticancer agent from a vessel into the close tissues, is an uninvited and difficult problem that can lead to permanent local harms and severe disability. Objectives: To assess nurse’s knowledge about management extravasation vesicant intravenous cytotoxic medication. Methodology: Descriptive design using a self-administered questionnaire was employed. At al-Amal national hospital for tumor treatment in Baghdad city from 2nd December 2018 to 10th February 2019). Random sampling method. The sample size was 45 nurses completed a questionnaire about management extravasation vesicant intravenous chemotherapy. Instruments: developed by the researcher consist of three sections the first section to assess the demographic data. And the second section questionnaire consists of 20 items divided into two parts to measure the information of team nurses on vesicant drug and management extravasation Vesicant intravenous chemotherapy. Data analysis by using the Statistical Package for Social Sciences version (SPSS) 23.0 included. (Frequency, percentage, Kruskal Wallis H test, Chi-square test, and Mann-Whitney U test). The level of significance was the threshold at p<0.05. Results: shows that the high percentage (42.2%) of oncology nurses ages (30-39 years old). Most of them (57.8 %) were female. The education level represents (42.2%) of nurses were from nursing institute graduates, the high percentage (46.7%) of them their experience in oncology unite were (5-9) years. Mostly no training session. Inferential there are statistically significant between education levels groups the nursing college showed a higher mean knowledge score than other levels. also, a higher significantly difference was observed between mean knowledge and participate with Training courses by mean (36.40) The researcher decide that nurse’s knowledge is the poor component about vesicant cytotoxic and management extravasation according to of assessment result Conclusion: there is a need for structuring a permanent education program due to the poor scientific of nurse’s knowledge about the vesicant and management of extravasation by chemotherapeutic drugs. Therefore, the issue of training courses should be highlighted for it is an effective role in improving the performance of nurses.